SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODEL VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP SIKAP SOSIAL SISWA SEKOLAH DASAR - Saskia Rahma Gita; Yosep Aspat Alamsyah; Muhammad Muchsin Afriyadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The development of social attitudes among elementary school students has gained increasing attention due to the growing need for learners to interact effectively, collaborate with others, and adapt to diverse social environments. Although the Value Clarification Technique (VCT) has been widely implemented in values-based learning, empirical findings regarding its effectiveness remain dispersed across different educational contexts, subject areas, and research designs, resulting in a fragmented body of evidence. This study was conducted to map and synthesize research findings concerning the contribution of VCT to the development of social attitudes among elementary school students. A literature search was carried out through Google Scholar, Garuda, and other scientific databases with the assistance of Publish or Perish. Of the 1,248 articles initially identified, 22 met the inclusion criteria after undergoing a multi-stage screening process based on the PRISMA 2020 framework. The collected data were analyzed using narrative synthesis to identify recurring findings, implementation characteristics, and factors influencing the effectiveness of the model. The synthesis revealed a consistent pattern of improvement in cooperation, tolerance, responsibility, social awareness, and students’ ability to respect others’ opinions following the implementation of VCT. Beyond its contribution to social attitude development, several studies also reported positive effects on character formation, learning motivation, and critical thinking skills. These outcomes tended to be more pronounced when the value clarification process was supported by instructional media that encouraged active student participation. The findings suggest that VCT serves as a values-based instructional approach that not only fosters social attitude development but also enhances the overall quality of elementary students’ learning experiences. ABSTRAK Penguatan sikap sosial pada siswa sekolah dasar menjadi perhatian yang semakin penting seiring meningkatnya kebutuhan akan kemampuan berinteraksi, bekerja sama, dan hidup dalam lingkungan yang beragam. Meskipun Value Clarification Technique (VCT) telah banyak diterapkan dalam pembelajaran berbasis nilai, temuan empiris mengenai efektivitasnya masih tersebar pada berbagai konteks, mata pelajaran, dan desain penelitian sehingga belum memberikan gambaran yang terintegrasi. Kajian ini dilakukan untuk memetakan dan mensintesis bukti-bukti penelitian terkait kontribusi VCT terhadap perkembangan sikap sosial siswa sekolah dasar. Proses penelusuran literatur dilakukan melalui Google Scholar, Garuda, dan berbagai basis data ilmiah lainnya dengan bantuan Publish or Perish. Dari 1.248 artikel yang teridentifikasi pada tahap awal, sebanyak 22 artikel memenuhi kriteria inklusi setelah melalui proses seleksi bertahap mengacu pada alur PRISMA 2020. Data yang diperoleh dianalisis menggunakan narrative synthesis untuk mengidentifikasi kecenderungan temuan, karakteristik implementasi, serta faktor yang memengaruhi efektivitas model. Sintesis menunjukkan adanya pola yang konsisten berupa berkembangnya kerja sama, toleransi, tanggung jawab, kepedulian sosial, dan kemampuan menghargai pendapat orang lain setelah penerapan VCT. Selain berkaitan dengan penguatan perilaku sosial, beberapa penelitian juga memperlihatkan kontribusi terhadap karakter, motivasi belajar, dan kemampuan berpikir kritis. Efektivitas tersebut cenderung lebih optimal ketika proses klarifikasi nilai didukung oleh media pembelajaran yang mendorong partisipasi aktif peserta didik. Temuan ini menegaskan bahwa VCT berfungsi sebagai pendekatan pembelajaran berbasis nilai yang tidak hanya mendukung perkembangan sikap sosial, tetapi juga memperkuat kualitas pengalaman belajar siswa sekolah dasar secara lebih menyeluruh.